Enhanced and long-lasting SARS-CoV-2 immune memory in individuals with common cold coronavirus cross-reactive T cell immunity - Florian, David M.; Bauer, Michael; Popovitsch, Amelie; Fae, Ingrid; Springer, David N.; Graninger, Marianne; Traugott, Marianna; Weseslindtner, Lukas; Aberle, Stephan W.; Fischer, Gottfried; Kundi, Michael; Stiasny, Karin; et al. (Frontiers in Immunology, 2025)
With the continuous emergence of novel SARS-CoV-2 variants, long-lasting and broadly reactive cellular and humoral immunity is critical for durable protection from COVID-19. We investigated SARS-CoV-2-specific T cell immunity in relation to antibodies, infection outcome and disease severity and assessed its durability in a longitudinal cohort over a three-year time course. We identified pre-existing T cells reactive to the seasonal coronavirus (CoV) OC43 that cross-react with the conserved SARS-CoV-2 spike S813-829 peptide. These cross-reactive T cells increased in frequency following SARS-CoV-2 infection or vaccination and correlated with enhanced spike-specific T cell responses and significantly reduced viral loads. Furthermore, our data revealed that CoV-cross-reactive T cells were maintained as part of the long-lasting memory response, contributing to increased T cell frequencies against omicron variants. These findings suggest a functional role of CoV-cross-reactive T cells that extends beyond the initial SARS-CoV-2 exposure, contributing to enhanced immunity against highly mutated SARS-CoV-2 variants.